Perancangan Hand Sanitizer Otomatis Berbasis Mikrokontroler Arduino Uno - Ramadian, Angga Putra; Marlinda, Linda (Sinkron : jurnal dan penelitian teknik informatika, 2021)
The current COVID-19 pandemic is still very worrying and still shows no sign of ending, the development of positive confirmed cases continues to increase every day, plus there are still many people around who wash their hands by touching hand washing tools directly. This is what makes the author to make hand sanitizer automatically. An automatic hand sanitizer that is used to help reduce or minimize direct contact in preventing the transmission of COVID-19 that is currently happening. Most hand washing tools, especially hand sanitizers, are used manually by pressing. Arduino is a single board microcontroller or board that is open source or open source, so we can use it or make modifications and it is specially designed to make it easier to create objects or develop electronic devices that can interact with various sensors or controllers, the hardware has an Atmel processor. AVR. Electromagnetic light which has a wavelength longer than visible light. One of the sensors that can be used to detect objects is an infrared sensor. Infrared wavelength is between 700nm to 1mm, that means this wave is longer than light wave and shorter than radio wave. This wave can be used as a short distance transmission medium because it cannot penetrate buildings and is susceptible to other electromagnetic waves. Infrared is in the frequency of 300GHZ to 400THz.